PERAN INSTAGRAM SEBAGAI MEDIA PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN REMAJA - Ahmad Burhanuddin; Caesario Razainur Harahap; Delipah Sari Pane; Siti Anum (Yayasan Baitul Hikmah al-Zain, 2026)
The rapid development of digital technology has significantly influenced the way information is delivered, including in the field of religious education. Instagram, as one of the most widely used social media platforms among teenagers, offers visually engaging features that can attract attention and enhance learning motivation. This study aims to analyze the role of Instagram as a medium of religious education in improving teenagers’ understanding of Islamic teachings. This research employs a qualitative method, with data collected through observing active Islamic educational accounts, interviewing several teenage Instagram users, and documenting various forms of religious content such as short videos, images, and infographics. The results of the study indicate that Instagram can serve as an effective medium for religious education, as the content presented is easier to understand, interactive, and relevant to the lives of teenagers. Creative delivery of religious messages encourages teenagers to learn Islamic values and apply them in their daily lives. However, the study also found challenges, including limited digital literacy and the risk of accessing inaccurate religious content. Therefore, guidance from educators or parents is needed to ensure that Instagram is utilized wisely and responsibly as a medium for religious education.